(untitled) (International Journal of Biology and Chemistry, 2025)
Rabies remains a serious global public health concern. The envelope glycoprotein of the rabies virus (RABV-G) is the principal viral antigen and harbors critical neutralizing epitopes, making it a promising target for subunit vaccine development and diagnostic applications. Nevertheless, the efficient production of recombinant RABV-G with preserved antigenic and immunogenic properties remains technically demanding. In this work, we developed an optimized strategy for the expression and purification of recombinant RABV-G and assessed its antigenicity and immunogenicity. The rabies virus glycoprotein ectodomain (rRABV-GE) was successfully expressed in Escherichia coli Rosetta2(DE3)pLysS and purified in a biologically relevant form. The rRABV-GE gene was codon-optimized and cloned into the pET-28c(+) expression vector, resulting in recombinant protein expression largely in an insoluble state. Consequently, the protein was subjected to refolding and purification procedures. To improve protein solubility, hydrophobic loop regions were substituted with flexible linker sequences. Protein purification was performed under denaturing conditions using urea, followed by affinity chromatography. The identity and antigenicity of the purified protein were confirmed by Western blot analysis and indirect enzyme-linked immunosorbent assay (ELISA). ELISA testing was performed using rabbit sera collected from animals immunized with the commercial Purified Vero Cell Rabies Vaccine (RHABDOVAC-1). Collectively, these findings indicate that the optimized bacterial expression platform enables the production of biologically relevant rRABV-GE and provides a cost-effective approach for the development of rabies subunit vaccines and diagnostic reagents. In summary, the recombinant rRABV-G protein produced in this study appears to be a suitable diagnostic antigen for ELISA-based and other rabies virus immunodiagnostic uses. Keywords: Rabies virus, glycoprotein ectodomain, antibody, ELISA, Rosetta2(DE3)pLysS, vaccine.